The role of nitric oxide and hydrogen sulfide in regulation of redox homeostasis at extreme temperatures in plants - Kolupaev, Yuriy E.; Yemets, Alla I.; Yastreb, Tetiana O.; Blume, Yaroslav B. (Frontiers in Plant Science, 2023)
Nitric oxide and hydrogen sulfide, as important signaling molecules (gasotransmitters), are involved in many functions of plant organism, including adaptation to stress factors of various natures. As redox-active molecules, NO and H2S are involved in redox regulation of functional activity of many proteins. They are also involved in maintaining cell redox homeostasis due to their ability to interact directly and indirectly (functionally) with ROS, thiols, and other molecules. The review considers the involvement of nitric oxide and hydrogen sulfide in plant responses to low and high temperatures. Particular attention is paid to the role of gasotransmitters interaction with other signaling mediators (in particular, with Ca2+ ions and ROS) in the formation of adaptive responses to extreme temperatures. Pathways of stress-induced enhancement of NO and H2S synthesis in plants are considered. Mechanisms of the NO and H2S effect on the activity of some proteins of the signaling system, as well as on the state of antioxidant and osmoprotective systems during adaptation to stress temperatures, were analyzed. Possibilities of practical use of nitric oxide and hydrogen sulfide donors as inductors of plant adaptive responses are discussed.